PENERAPAN E-GOVERNMENT DALAM MENDORONG TERWUJUDNYA PENYELENGGARAAN PEMERINTAHAN YANG BAIK (STUDI PENELITIAN KABUPATEN / KOTA DI JAWA TENGAH) - Herawati, Nunik Retno (JURNAL ILMU SOSIAL, 2014)
The implementation of e-government aims to establish a good relationship between the government and the society as well as businesses that take place in an efficient, effective and economical. In addition, the purpose of implementing e-government is to achieve a good governance (good governance). Good governance has several elements one of which is the effectiveness and efficiency.Departing from the above conditions, this study tried to describe the general adoption of e-Government Regency/City in Central Java. In detail, this study will discuss how the implementation of E Government Regency/City in Central Java and what the barriers to implementation of the E Government.Application of E Government by Regency City in Central Java, most of the entry on stage 2 (two), but there are some districts / municipalities that have entered at step 3 (three) which apply online application for public services. For institutions, the need for clarity of authority and responsibility of all agencies in the government district / municipality. Some of Regency/City there that give's responsibility in the development of E Government Electronic Data Processing Section (PDE) in the Regional Secretariat. However there are some Regency/city that provide responsibility under the Department of Transportation, Communication and other Information. Another problem encountered is the lack of ability of the ranks of civil servants and others in the field of ICT for the conduct of government in the Regional (E-Government) and lack of budget implementation of e-government.